The impacts of natural polyphenols and exercise alone or together on microRNAs and angiogenic signaling - Sun, Yanna; Chen, Linlin; Xiao, Lili; Wang, Xiaofang; Hallajzadeh, Jamal (Frontiers in Pharmacology, 2025)
microRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression at the RNA level. In recent decades, increasing evidence has shown that miRNAs play crucial regulatory roles in various biological processes and are considered promising targets for preventing and treating several diseases, including cardiovascular disorders. Multiple studies have suggested that miRNAs serve as significant modulators of angiogenesis. It is believed that the angiogenic response of the vascular endothelium is influenced by miRNAs, indicating a new perspective on the angiogenesis process. Exercise training is an effective strategy for enhancing cardiovascular health, partly due to its positive effects on lipid profiles and increased blood flow in vessels resulting from structural changes in the vasoreactivity of coronary arteries. The literature also provides evidence of polyphenols’ anti-inflammatory, antioxidant, antiviral, and anti-cancer properties across various organs. Polyphenols offer significant health benefits and are recognized for their role in preventing and treating multiple disorders, including cardiovascular disease. They can reduce the risk of ischemic stroke by mitigating platelet aggregation, dyslipidemia, and hypertension. To our knowledge, no current review comprehensively summarizes the combined effects of polyphenols and exercise on angiogenesis. Therefore, in the present review, we examined influence of polyphenols intake and exercise alone or together on angiogenic signaling via modulating the expression of miRNAs.